Ekstraksi Gliserin Dari Biodiesel Menggunakan Deep Eutectic Solvent Berbasis Asam Tanat-Cholin Chloride Sebagai Ekstraktan - Ola, Pius D.; Kusuma, Albert W.; Nitbani, Febri O.; Ola, Antonius R. B. (Universitas Nusa Cendana, 2022)
Biodiesel is a concern for many parties because it is environmentally friendly, non-toxic, and renewable. One of the problems faced in the use of biodiesel as an alternative energy is the process of purification from impurities and by-products such as glycerin which is complicated and expensive. Glycerin can cause saponification, increase ignition delay, incomplete combustion, blockage and increase engine maintenance costs. In this study, deep eutectic solvents (DES) synthesized from choline chloride (ChCl) salts and tannic acid were used as extractants for the extraction of glycerin from biodiesel synthesized through palm oil transesterification with methanol as a trans substituent and KOH as a catalyst. The effect of the composition of the constituent moles of DES and the ratio of biodiesel-DES mass to glycerin content of biodiesel has been studied. The results showed that the higher the content of ChCl salt in DES and the greater the ratio of biodiesel-DES, the lower the glycerin content in biodiesel, with the highest decrease of 65.7693% (glycerin content after extraction of 2.0193%) obtained from the composition of the mole DES 1:47 (Tannic acid:ChCl) and the mass ratio of biodiesel-DES 1:3. The biodiesel produced has not met SNI 1782, which is 0.02%.